Pengaruh Brand Image dan Lokasi terhadap Keputusan Calon Mahasiswa Melanjutkan Studi di Perguruan Tinggi - Neswardi, Sepri; Yuanita, Ika; Jumyetti, Jumyetti (Jurnal Ilmiah Poli Bisnis, 2022)
Brand Image is a determining factor in decision making. This study aims to determine whether brand image (brand image), location affect the decision of prospective students to continue their studies in college. The place of research is Padang State Polytechnic with 244 students who are the class of 2022 in the Department of Commerce Administration. The research method uses quantitative methods with data collection using questionnaires, primary data obtained using quantitative analysis with data processing tools using SPSS. Data analysis was performed with multiple linear regression (independent variables brand image and location, while dependent variable is decision making). The percentage contribution of the influence of brand image and location variables on purchasing decisions is 46%, while the rest (100% - 46% = 54%) is influenced by other variables that are not taken into account in this study. The limitation of this research is that the number of samples is still small, namely 244 people and further research can be carried out with a large sample with the addition of other variables as factors that influence DNA, which can also be done with a mix method.